The Role of the Bumiputera Press in the Indonesian National Movement in the Early 20th Century - Widianto, Retno; Djono, Djono; Ediyono, Suryo (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This article aims to: (1) Explain the emergence of Bumiputera press, (2) Explain the struggle of the Indonesian national movement in the early 20th century, (3) Explain the role of Bumiputera Press in the Indonesian national movement. The author uses methods in historical research that consist of several stages, namely: collecting sources, source criticism, interpretation, and historiography. The results of this article indicate that: (1) The emergence of Bumiputera press was supported by the development of education in the Dutch East Indies, (2) The emergence of educated people became the driving force behind the birth of the Indonesian national movement, (3) Bumiputera Press served as a tool to voice the interests of the people against the injustices of colonial and feudal rulers and as a medium of provocation to awaken the courage of the common people against the ruling groups.